2023
DOI: 10.1038/s41467-023-38281-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular architecture of the Gαi-bound TRPC5 ion channel

Abstract: G-protein coupled receptors (GPCRs) and ion channels serve as key molecular switches through which extracellular stimuli are transformed into intracellular effects, and it has long been postulated that ion channels are direct effector molecules of the alpha subunit of G-proteins (Gα). However, no complete structural evidence supporting the direct interaction between Gα and ion channels is available. Here, we present the cryo-electron microscopy structures of the human transient receptor potential canonical 5 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 90 publications
0
9
0
Order By: Relevance
“…The ability to observe different types of water molecules in membranes and the feasibility of differentiation of the environment in ion channels by 17 O NMR experiments are unique and exciting. The use of nanodiscs to measure residual 17 O quadrupole couplings to study the structure and dynamics of membrane-bound water and to study the phase transition of encased lipids opens new avenues in membrane biophysics. The fact that water plays a crucial role in biology and the advent of higher magnetic fields and better NMR instrumentations renders more sophisticated NMR techniques, the benefits of 17 O based NMR applications can be expected to grow remarkably. Therefore, we conclude that much remains to be done to fully utilize the power of 17 O based NMR spectroscopy to study biological solids.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…The ability to observe different types of water molecules in membranes and the feasibility of differentiation of the environment in ion channels by 17 O NMR experiments are unique and exciting. The use of nanodiscs to measure residual 17 O quadrupole couplings to study the structure and dynamics of membrane-bound water and to study the phase transition of encased lipids opens new avenues in membrane biophysics. The fact that water plays a crucial role in biology and the advent of higher magnetic fields and better NMR instrumentations renders more sophisticated NMR techniques, the benefits of 17 O based NMR applications can be expected to grow remarkably. Therefore, we conclude that much remains to be done to fully utilize the power of 17 O based NMR spectroscopy to study biological solids.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…There is a possibility that ion channels and GPCRs may coexist in close proximity, forming a signaling cluster within a specific region of the plasma membrane ( Neves et al, 2002 ). The recent cryo-EM structure demonstrated that Gα i3 could directly activate the TRPC5 channels, and the channel requires both Ca 2+ and PIP 2 as essential cofactors for the complete activation of Gα i3 ( Won et al, 2023 ).…”
Section: Two Major Kinds Of G Protein: Small G Protein and Heterotrim...mentioning
confidence: 99%
“…Initial studies suggested that the binding sites for G protein exist at the rib helix of TRPC4/5 channels or the CIRB domain ( Jeon et al, 2012 ). However, recent cryo-EM structure showed that IYY 58-60 amino acids at ARD bind with G i3 protein ( Won et al, 2023 ). Main debate concerns with the role of PIP 2 .…”
Section: Trpc4/5 Activation Mechanism: Pip 2 Ca ...mentioning
confidence: 99%
See 2 more Smart Citations